Biometric identification in electronic voting systems - Ibañez, Eduardo (2009)
An extension of previous developments of electronic voting and e-government systems carried out at the School of Computer Science of the UNLP is presented, where a digital fingerprint recognition feature is added to the existing system used for faculty elections at this School.\nThe characteristics and performance of the biometric recognition system are analyzed, as well as the modification of the on-site electronic voting system used in La Plata (hardware and software) and the adaptation to an Internet voting system that can be used at Regional Centers.\nFinally, the generalizations of the use of the technology developed for e-government are discussed and current research and development lines are mentioned.